Go Green: Strategi Santri Menjaga Lingkungan Dalam Perspektif Maqashid Syariah - Anwar, Khairul; Susminingsih, Susminingsih (Rumah Jurnal Institut Agama Islam An-Nawawi Purworejo, 2024)
Go green activities must be carried out by all parties, including students. Students who have been equipped with religious knowledge must implement it in protecting and caring for the environment. This research aims to determine and analyze the role of santri in protecting the environment, as well as analyzing the concept of protecting the environment from a maqashid sharia perspective. This research was conducted using library research methods, using a qualitative approach. The data source used is a secondary data source. namely collecting, understanding, and analyzing previous articles, news and books on relevant topics, be it journal articles, news in online media, and books that discuss environmental issues. The data collection techniques used in this research are literature and documentation. The data analysis technique used in this research is the descriptive method. The research results explain that in environmental conservation, students who have been equipped with religious knowledge in Islamic boarding schools, majlis or other places, must have full awareness of the balance of nature. These go green activities or activities are very much in line with the principles of maqashid sharia, which aim to achieve the benefit of humans and other living creatures. Keywords: Santri, Environment, Maqashid Syariah.